1958
DOI: 10.2136/sssaj1958.03615995002200020016x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Survey Interpretation-Theory and Purpose

Abstract: Soil survey interpretation comprises the organization and presentation of knowledge about characteristics, qualities, and behavior of soils as they are classified and outlined on maps. This knowledge should be organized and presented in ways that will help people to make more intelligent decisions in their uses of soils. Agricultural users should be helped to make proper choices from available alternatives in use and management of soils for plant production. Engineering users should be helped to make choices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Yield prediction is a fundamental part of soil survey and interpretation. Soil Survey Staff (1951), Aandahl (1958), Odell (1958), and Kellogg (1961) stressed the importance of accurate and reliable crop yield estimates by soil taxonomic unit. Productivity indexes represent soil‐crop yield relationships and provide a basis for land‐use planning, land valuation, and estimating potential economic return.…”
mentioning
confidence: 99%
“…Yield prediction is a fundamental part of soil survey and interpretation. Soil Survey Staff (1951), Aandahl (1958), Odell (1958), and Kellogg (1961) stressed the importance of accurate and reliable crop yield estimates by soil taxonomic unit. Productivity indexes represent soil‐crop yield relationships and provide a basis for land‐use planning, land valuation, and estimating potential economic return.…”
mentioning
confidence: 99%
“…Statistical models were calibrated against the properties of the soils and yields were estimated for three crops representing 25 soils and 5 great groups. Aandahl (1958) and Kellogg (1961) emphasized the need for reliable crop yield estimates by soil series. Kellogg (1961) suggested that yield tables are the most important part of the soil interpretation process.…”
mentioning
confidence: 99%
“…Selected soil properties and management practices must be determined to make maximum use of the data (Krantz, 1958). Aandahl (1958) recommended using benchmark soils in all productivity studies.…”
mentioning
confidence: 99%
“…The need for accurate and reliable yield estimates by soil taxonomic unit has been emphasized by many researchers (Aandahl, 1958; Kellogg, 1961). Yield data are used to develop productivity indexes that are useful in technology transfer, farm enterprise budgeting, erosion research, soil correlation, and other soil interpretations.…”
mentioning
confidence: 99%